1998
DOI: 10.1046/j.1365-2699.1998.252191.x
|View full text |Cite
|
Sign up to set email alerts
|

Bill and body size in the peregrine falcon, north versus south: is size adaptive?

Abstract: Visually, the bill size on southern hemisphere peregrine falcons (Falco peregrinus), especially from Australasia and the Philippines, appears appreciably larger for their body size than in other peregrine populations. Accordingly, we measured the bill ‘size’ or ‘volume’ (length, width, depth) as a function of body mass on a sample of peregrines. We used both wing and tarsal length as indicators of body mass. We compared bill volume between two northern hemisphere groups, a medium‐sized tundra breeding group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
(2 reference statements)
2
11
1
Order By: Relevance
“…The smallest subspecies Falco peregrinus minor, found in Africa, for example, is less than half the size of the largest subspecies Falco peregrinus pealei, which is found in the northwest regions of North America (Jenkins, 1995;Johansson, Linder, Hardin, & White, 1998).…”
Section: Intraspecific Gene Flow Local Adaptation and Extraordinamentioning
confidence: 98%
See 1 more Smart Citation
“…The smallest subspecies Falco peregrinus minor, found in Africa, for example, is less than half the size of the largest subspecies Falco peregrinus pealei, which is found in the northwest regions of North America (Jenkins, 1995;Johansson, Linder, Hardin, & White, 1998).…”
Section: Intraspecific Gene Flow Local Adaptation and Extraordinamentioning
confidence: 98%
“…These subspecies have the potential to locally adapt to their endemic prey and conditions and can display very marked differences in phenotypes. The smallest subspecies Falco peregrinus minor , found in Africa, for example, is less than half the size of the largest subspecies Falco peregrinus pealei , which is found in the northwest regions of North America (Jenkins, ; Johansson, Linder, Hardin, & White, ). Behavioral difference can also be pronounced: Some subspecies are migratory, whereas others are not and differences in nesting habits, breeding seasons, and prey choice have also been documented between subspecies (see White, Cade, et al, for a thorough review of differences between peregrine subspecies).…”
Section: Genomics and Falcon Diversity As A Research Systemmentioning
confidence: 99%
“…Falcons, however, tend to employ their jaws by delivering powerful bites to the neck to kill their victims by breaking the cervical vertebrae and damaging the spinal cord (Cade, 1982;Hertel, 1995) (but see . Previous studies have demonstrated how morphological characteristics of the beaks (Bierregaard, 1978;Hull, 1991;Hertel, 1994a;Hertel, 1995;Johansson et al, 1998;Dzerzhinsky and Ladygin, 2004) and hind limbs (Bierregaard, 1978;Hertel, 1994b;Ward et al, 2002;Einoder and Richardson, 2007a) of raptorial birds are related to differences in diet and/or feeding behavior across groups. For instance, Hertel (Hertel, 1995) found suites of skull, maxillary and mandibular characteristics that served to discriminate among trophic specialists; whereas bird-eaters tend to have wide skulls and beaks with increased mechanical advantage, scavengers tend have narrow beaks with greater curvature.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal variation in bird morphology has been detected over relatively short periods: 50 years in the fox Sparrow (Passerella iliaca; Zink 1983), 10 years in the Song Sparrow (Melospiza melodia; Marshall 1948), and, within the genus Accipiter, 30 years (Tornberg et al 1999). Last, most older museum specimens lack data on body mass, precluding any adjustment for variation in measurements as a function of mass (size) (Askenmo 1982, Zink and Remsen 1986, Mcgillivray 1987, Johansson et al 1998. for theoretical and empirical reasons, mass is considered by many to be the most accurate univariate measure of body size in birds (Cade 1960, Mueller 1986, Mcgillivray 1987, Marti 1990, Dunning 2008.…”
mentioning
confidence: 99%
“…Because ANOVA revealed a difference in mass by site for both sexes and because other mensural characters may be attributable to body mass or size (Askenmo 1982, Johansson et al 1998, Rosenfield and Bielefeldt 1999, Dunning 2008, we tested each character with ANCOVA to search for differences in morphology among geographic regions as a function of mass (i.e., did birds of the same mass differ significantly by site in other attributes). In ANCOVA the treatment was the geographic region, the dependent variables were the morphological characters, and the covariate was mass.…”
mentioning
confidence: 99%